Testes de vigor em sementes de quiabeiro - Lopes, Magnólia de Mendonça [UNESP] (Universidade Estadual Paulista (Unesp), 2007)
The objective of this research was to study the physiological tests of controlled deterioration, accelerated aging, electrical conductivity and potassium leakage, for okra seeds, to evaluate it’s physiological quality. The experiment was carried out by using four okra seed lots cv. “Santa Cruz”. In the first stage were performed the standard germination, first germination count, speed of germination index, field seedling emergence, controlled deterioration seed (water content of 18, 21 and 24%, 45ºC, during 24 hours). The accelerated aging with and without salt solution with period of 48, 72, 96 and 120 hours at 41 and, 45ºC. For the electrical conductivity were used temperatures of 25 and, 30ºC, volumes of 25 and 50 mL of water, 25 and 50 seeds and periods of 1, 2, 4, 6, 12, 18 and, 24 hours. The potassium leakage (25 seeds, 25mL of water at 25ºC during 2, 4, 6, 12, 18 and 24 hours. In the second stage, the procedure considered more relevant for every test was repeated. According to the obtained results was concluded that the controlled deterioration test with 24% of seed water content at 41ºC for 24 hours. The accelerated aging with and without salt solution using 41ºC for 72 hours and the electrical conductivity test 25 seeds with 25mL of water at 25ºC during 24 hours were the most indicated tests to evaluate the physiological seed quality of okra seeds. The potassium leakage needs additional studies to adequate it’s methods and to make viable it’s use for okra seeds.

Essa pesquisa teve como objetivo adequar os testes de deterioração controlada, de envelhecimento acelerado, de condutividade elétrica e de lixiviação de potássio, na avaliação da qualidade fisiológica de sementes de quiabo (Abelmoschus esculentus (L.) Moench). O experimento foi conduzido utilizando-se quatro lotes de sementes de quiabo, cv. Santa Cruz. Na primeira etapa do trabalho foram realizados os testes de germinação, primeira contagem da germinação, índice de velocidade de germinação, emergência de plântula em campo e estudos específicos para os testes de deterioração controlada (teores de água de 18, 21 e 24%, temperaturas de 41 e 45ºC durante 24 horas). O envelhecimento acelerado, com e sem solução salina (períodos 48, 72, 96 e 120 horas, a 41ºC e 45ºC). A condutividade elétrica (temperaturas de 25 e 30ºC, volumes de 25 e 50 mL de água, 25 e 50 sementes e períodos de 1, 2, 4, 6, 12, 18 e 24 horas). A lixiviação de potássio (25 sementes, 25 mL de água a 25ºC, durante 2, 4, 6, 12, 18 e 24 horas). Na segunda etapa, os procedimentos considerados mais promissores para cada teste na primeira etapa, foram repetidos. De acordo como os resultados obtidos, concluiu-se que os testes de deterioração controlada com 24% de teor de água das sementes a 41ºC por 24 horas, o envelhecimento acelerado com e sem solução salina utilizando 41ºC por 72 horas e o teste de condutividade elétrica, 25 sementes com 25mL de água a 25ºC durante 24 horas foram os testes mais indicados para avaliação da qualidade fisiológica de sementes de quiabo. O teste de lixiviação de potássio necessita de estudos adicionais para adequar seu método e viabilizar a sua utilização para sementes de quiabo.
Keywords: Controlled deterioration; accelerated aging; Electrical conductivity; Potassium leakage; Sementes - Qualidade - Envelhecimento; Condutividade elétrica; Abelmoschus esculentus (L.); Deterioração controlada; Lixiviação de potássio